PENGEMBANGAN SOAL TES KEMAMPUAN REPRESENTASI DAN PENALARAN MATEMATIS SERTA SKALA SIKAP SELF CONCEPT UNTUK SISWA SMP - Lisa Dwi Afri (State Islamic University of North Sumatra, 2019)
The ability of representation and mathematical reasoning is a mathematical ability that must be developed at every level of education. In addition to these cognitive aspects, affective aspects must also be developed in learning. One of which is the student's self concept. To find out the development of mathematical representation and reasoning abilities, as well as students' self concept, an evaluation tool is needed. This is the reason of the authors doing this research to produce reliable and accountable evaluation tools. The step of the research is compiling the grid, compiling the items test questions the ability of representation and mathematical reasoning as well as compiling the points of the statement of the scale of the self concept, validating with experts, conducting trials, scoring, and analyzing the characteristics of items. The results obtained are a reliable evaluation tool to measure the ability of representation and mathematical reasoning as well as the self concept of elementary students.